Everest: Scaling down peak loads through I/O off-loading - Narayanan, Dushyanth; Donnelly, Austin; Thereska, Eno; Elnikety, Sameh; Rowstron, Antony; Rowstron, Ant (Proceedings of 8th USENIX Symposium on Operating Systems Design and Implementation (OSDI '08), 2008)
Bursts in data center workloads are a real problem for storage subsystems. Data volumes can experience peak I/O request rates that are over an order of magnitude higher than average load. This requires signiﬁcant overprovisioning, and often still results in signiﬁcant I/O request latency during peaks. In order to address this problem we propose Everest, which allows data written to an overloaded volume to be temporarily off-loaded into a short-term virtual store. Everest creates the short-term store by opportunistically pooling underutilized storagere sources either on a server or across servers within the data center. Writes are temporarily off-loaded from overloaded volumes to lightly loaded volumes, thereby reducing the I/O load on the former. Everest is transparent to and usable by unmodiﬁed applications,and does not change the persistence or consistency of the storage system. We evaluate Everest using traces from a production Exchange mail server as well as other benchmarks: our results show a 1.4–70 times reduction in mean response times during peaks